2021
DOI: 10.1097/tp.0000000000003839
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Lung Allograft and Clinical Outcomes in Lung Transplant Recipients: A Case-control Study

Abstract: Background. The impacts of COVID-19 on lung allograft function, rejection, secondary infection, and clinical outcomes in lung transplant recipients (LTRs) remain unknown. Methods. A 1:2 matched case–control study was performed to evaluate rehospitalization, lung allograft function, and secondary infections up to 90 d after COVID-19 diagnosis (or index dates for controls). Results. Twenty-four LTRs with COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 43 publications
2
42
3
Order By: Relevance
“…The analysis shows a 28‐day, and overall mortality following COVID‐19 in this unselected LTx population of 4.2% and 14.8%, respectively. The 28‐day mortality is lower than in previously published LTx cohorts (9–34%) [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The analysis shows a 28‐day, and overall mortality following COVID‐19 in this unselected LTx population of 4.2% and 14.8%, respectively. The 28‐day mortality is lower than in previously published LTx cohorts (9–34%) [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Discussioncontrasting
confidence: 54%
“…There are few studies with available pre‐COVID‐19 FEV1 from healthy patients to explore the course of FEV1 dynamic post‐COVID‐19 in nontransplanted patients, and there is only limited evidence that worse symptoms are associated with lower post‐COVID‐19‐FEV1 in a nontransplanted population [ 27 ]. Interestingly, a recent study found no significant difference in the loss of lung function between LTx recipients with COVID‐19 patients and matched controls over 90 days [ 9 ]. However, no detailed information on disease severity at presentation was included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post‐acute illness outcomes in the current report appear worse than the only other study evaluating post‐discharge outcomes among COVID‐19 patients, where an FEV1 decline > 10% was noted among five out of the 21 patients. 19 However, the differences are possibly linked to the variability in study design, inclusion criteria, and definition of endpoints. It appears that COVID‐19 patients in the current study ( n = 54) had more risk factors for the severe disease at presentation, as a higher proportion of patients had pertinent comorbidities such as diabetes (48.1%) and stage 3 or worse chronic kidney disease (46.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the follow‐up period of the study by Permpalung et al. 19 was limited to 90 days which may have under‐estimated the post‐infection loss in lung functions.…”
Section: Discussionmentioning
confidence: 99%